Nutritional of at-Talbinah in Depression’s Management: Analysis from the Classic and Contemporary Muslim Scholars - Nazri, Mohd Arif; Mustapha, Ariyanti; Kamaruddin, Zuraidah; Che Haron, Sueraya (ADDIN, 2024)
Depression is a common mental disorder that affects various aspects of life. The increasing prevalence of depression has led to excessive use of medication, which can have negative impacts on the body. Islam emphasizes the significance of Sunnah food, which is scientifically proven to be a natural and harmless remedy for the body. The objective of this article is to examine the nutritional benefits of at-talbinah and to highlight the importance of using diet to manage depression, thereby reducing the use, cost, and side effects of antidepressant medications. The significance of this qualitative study necessitated the systematic collection of comprehensive and detailed data from the six canonical books of hadith, significant books of interpretations, and scientific findings. The study discovered that regular intake of at-talbinah positively impacts mood and depression, as it can rejuvenate and strengthen the heart, as stated in hadiths. This effect is attributed to substances in at-talbinah that can control blood pressure, preventing feelings of depression. Studies concluded that the chemical elements in at-talbinah positively affect the connection between nerve cells, which helps relieve sadness and elevate a sense of satisfaction, relief, and happiness, as mentioned in the hadiths.